2017
DOI: 10.33584/jnzg.2017.79.560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autumn regrowth interval and nitrogen fertiliser on dry matter yield and plant characteristics of six forage species

Abstract: Abstract Cold temperatures and drainage increase nitrogen (N) losses from livestock production systems, so autumn management and forage type were investigated as strategies to mitigate N loss whilst meeting animal requirements. The effect of regrowth interval and fertiliser rate on plant dry matter (DM) yield, plant N and digestible organic matter in the DM (DOMD) was measured in six forage species over 4 weeks regrowth, in Canterbury in autumn 2015. As regrowth interval increased, herbage DM yield inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At Awanui, compared to perennial ryegrass, differences in seasonal DM yield could have been worth approximately $470 and $690/ha for tall fescue and cocksfoot, respectively. Both tall fescue and cocksfoot are generally accepted to have lower quality than perennial ryegrass (e.g., Martin et al 2017) which could diminish the value of this potential yield advantage. Griffiths et al (2020) reported a 12.3 kg MS/ha increase in production from an increase in ME of 0.1 MJ/kg DM.…”
Section: Perennial Grass Trialsmentioning
confidence: 99%
“…At Awanui, compared to perennial ryegrass, differences in seasonal DM yield could have been worth approximately $470 and $690/ha for tall fescue and cocksfoot, respectively. Both tall fescue and cocksfoot are generally accepted to have lower quality than perennial ryegrass (e.g., Martin et al 2017) which could diminish the value of this potential yield advantage. Griffiths et al (2020) reported a 12.3 kg MS/ha increase in production from an increase in ME of 0.1 MJ/kg DM.…”
Section: Perennial Grass Trialsmentioning
confidence: 99%
“…Recent research trials in warm (Waikato) and cool (Canterbury) regions of NZ were established to identify which forages, and management practises, resulted in lower herbage N (or crude protein concentration, which is assumed to be 16% N). Results regarding nutritive value and management responses have been published for the cool (Box et al 2017a;Martin et al 2017a;Martin et al 2017b) and warm (Dodd et al 2017) regions. In the cooler region, with long-term average air temperature differing by ∼4 degrees C compared to the warm region, grasses had the lowest herbage N concentration (mean of 2.7% for perennial ryegrass, Italian ryegrass, tall fescue, cocksfoot and prairie grass) followed by herbs (mean of 3.1% for chicory and plantain).…”
Section: Reduced Herbage N Concentrationmentioning
confidence: 99%
“…There is little scope for reducing perennial ryegrass N requirements through conventional plant breeding because there is very little intra-species variation (Chapman et al, 2015). These high CP and RDP concentrations in pasture can be further exacerbated by short regrowth intervals between grazings and by N fertilizer inputs (Martin et al, 2017).…”
mentioning
confidence: 99%